Remove repeated code - Contieri, Maximiliano (O'Reilly Media, Inc., 2024)
This collection is designed to equip developers with practical strategies and techniques for writing high-quality, maintainable code in contemporary software development environments. Clean code significantly impacts the efficiency of software development processes, the ease of collaboration within teams, and the long-term maintainability of projects. Using these shortcuts, software engineers can enhance their coding skills, improve code readability, reduce technical debt, and ultimately deliver more robust and scalable software solutions. The collection addresses common challenges such as debugging errors, refactoring, writing tests, making peer reviews and ensuring code consistency across projects. Developers will learn valuable skills such as effective code structuring, writing meaningful variable and function names, implementing design patterns, leveraging automation tools for code formatting and testing, and adopting principles like SOLID and DRY. This collection also includes guidance on writing and reviewing AI-generated clean code.
Keywords: Computer programming; Coding theory; Programmation (Informatique); computer programming